Community-Based Plastic Waste Pyrolysis in Mattiro Ade Village: Converting Waste Into Alternative Fuel - Lagu, Abdul Majid HR.; Jastam, Muh. Saleh (Universitas Islam Negeri Alauddin Makassar, 2026)
Growing interest in plastic waste valorization has highlighted the potential of pyrolysis technology; however, its community-level application remains limited, particularly in rural waste management systems. This community engagement program aimed to strengthen local capacity by implementing pyrolysis technology to convert plastic waste into alternative fuel in Mattiro Ade Village, Pinrang Regency, Indonesia. The program adopted a participatory approach integrating Community-Based Research and Participatory Action Research. Activities included preparation, pyrolysis unit fabrication, operational testing, community outreach, practical training, and transfer of the unit to the local Reduce, Reuse, Recycle Waste Processing Facility. Qualitative evaluation was conducted through participatory observation of community understanding, involvement, and operational readiness. The results showed improved awareness of plastic waste management, active community participation, and adequate readiness among local operators to use the pyrolysis unit. The initiative also demonstrated the feasibility of introducing small-scale pyrolysis within a community-based waste management framework. By linking plastic waste reduction with alternative fuel production, this program offers a practical pathway for strengthening local environmental governance and promoting circular resource use. Further implementation should prioritize technical assistance, routine monitoring, and fuel quality assessment to support operational sustainability and replication in comparable rural communities.